Implementación de refrigeración por ventilador en el establo para mejorar elmicroclima y la producción de leche de las vacas lecheras - Ruban, Sergiy (2025)
The aim of this study was to investigate the impact of fan cooling during high-temperature periods on barn microclimate, cow productivity, milk composition, and clinical indicators. The research was conducted at a commercial farm (Ukraine) where dairy cows were kept in two easy-to-assemble barns (with and without fans) during thermo-neutral and hot periods. The use of fans in the cowshed during the hot period helped to reduce the average daily temperature and relative humidity by 3.29 ºC and 1.88%. Indicators of rectal temperature and respiration rate at keeping in a barn with the use of fans were respectively: 0.35 ºC and 8.36 breaths/min compared to a barn without fans. The average milk yield in a barn with fans during the hot period decreased by 0.37 kg, and in a barn without fans by 2.64 kg compared to the thermo-neutral period. When keeping cows in a barn with fans during the hot period, the content of fat, protein and lactose in milk decreased by 0.03; 0.02 and 0.03%, while in a barn without fans, these figures were: 0.11; 0.06 and 0.07%, respectively. Increasing of average daily air temperatures was a significant stressor for lactating cows housed in barns without fans. Implementing fans in barns during hot periods positively affected the microclimate, improving temperature, relative humidity, and climate indices.